The Library of the Kamojys Parish Church in the Seventeenth Century - Paknys, Mindaugas (Senoji Lietuvos literatūra, 2024)
The article deals with the library of the Kamojys church that was inventoried during the visitation of the church in 1654. It also includes a description of the library and a discussion of the kind of books they might have been. The parish church of Kamojys in the Sviriai deanery of the Vilnius diocese has long attracted attention for its exceptional architecture. In the early seventeenth century, the massive two-tower brick church was still an exception rather than the rule in a province of the time. The architecture of the church, which was quite modern for the period, was also an attraction. However, the history of the parish has not been studied in detail. This article focuses mostly on the collection of books in the library of the Kamojys church, which was unusually large in the practice of the Vilnius diocese in the mid-seventeenth century. At that time, the libraries of parish churches consisted of only a dozen or so books on average, while in Kamojys, a collection of about two hundred books was inventoried, and these were not the books that were concerned with liturgical or pastoral activities alone. The library contained a number of Classical authors, medieval writers, historical books, religious polemics, books classified as heretic, publications on fish, plants, midwifery, and even a Muslim book in Turkish. In 1606, the church in Kamojys was funded by Jonas Rudamina Dusetiškis (Jan Rudomina Dusiacki, c. 1543–1621), but it was his son Petras Rudamina Dusetiškis (Piotr Rudomina Dusiacki, died in 1649) who paid even more attention to it. It was his milieu that initiated the larger part of this collection of books, which later ended up in the Kamojys church in one way or another. The article discusses, in general terms, the history of the Kamojys church, its founders, and the collection of books inventoried in the seventeenth century and analyses the kind of books, their authors, and the fate of the library. Although the article does not offer a typical picture of a parish church library of the mid-seventeenth century, the discussion of the collection gives a better general understanding of the libraries of the nobility at that time and the books that used to be collected and read.
Keywords: Grand Duchy of Lithuania; the Catholic Church; parishes; Kamojys; nobility; Rudamina Dusetiškis; Rudomina Dusiacki; funding; libraries; books; early literature